2004
DOI: 10.1186/1471-2334-4-61
|View full text |Cite
|
Sign up to set email alerts
|

Micronutrient malnutrition and wasting in adults with pulmonary tuberculosis with and without HIV co-infection in Malawi

Abstract: Background: Wasting and micronutrient malnutrition have not been well characterized in adults with pulmonary tuberculosis. We hypothesized that micronutrient malnutrition is associated with wasting and higher plasma human immunodeficiency virus (HIV) load in adults with pulmonary tuberculosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

14
76
0
4

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(102 citation statements)
references
References 23 publications
(12 reference statements)
14
76
0
4
Order By: Relevance
“…In comparison, 60% of malnourished tuberculosis patients with unknown HIV status were anemic in Indonesia (Karyadi et al, 2000), and 71% of adults co-infected with tuberculosis and HIV were anemic in Uganda (Shah et al, 2001). The relatively higher prevalence of anemia in Malawi is consistent with the observation that malnutrition and wasting are also higher in this study population compared with other populations of adults with pulmonary tuberculosis (van Lettow et al, 2004). In this study, we demonstrate an association between selenium deficiency and anemia in adults with pulmonary tuberculosis.…”
Section: Discussionsupporting
confidence: 79%
“…In comparison, 60% of malnourished tuberculosis patients with unknown HIV status were anemic in Indonesia (Karyadi et al, 2000), and 71% of adults co-infected with tuberculosis and HIV were anemic in Uganda (Shah et al, 2001). The relatively higher prevalence of anemia in Malawi is consistent with the observation that malnutrition and wasting are also higher in this study population compared with other populations of adults with pulmonary tuberculosis (van Lettow et al, 2004). In this study, we demonstrate an association between selenium deficiency and anemia in adults with pulmonary tuberculosis.…”
Section: Discussionsupporting
confidence: 79%
“…Similar findings were found for age, ethnicity and MUAC. Our findings are in line with the study in Malawi that found vitamin A deficiency, and not zinc deficiency, to be associated with wasting among TB patients, regardless of the HIV serostatus (van Lettow et al, 2004). In that study, vitamin A deficiency might have been influenced by the inflammatory process, but inflammation markers such as CRP were not measured.…”
Section: Discussionsupporting
confidence: 77%
“…Malnutrition in patients with tuberculosis has been documented in many studies [15][16][17] and is once again reflected in the above results. The present study demonstrated that BMI and MUAC were significantly lower before treatment and improved after treatment in both drug sensitive as well as drug resistant patients.…”
Section: Discussionsupporting
confidence: 61%